Como en el 99% de estos problemas pondremos todo en función del seno y el coseno
a)
$$\begin{align}&\frac{1}{sen^2u}-\frac{\cos^2u}{sen^2u}=\\ &\\ &\\ &\frac{1-\cos^2u}{sen^2u}=\frac{sen^2u}{sen^2u}=1\end{align}$$
b)
$$\begin{align}&\frac{senu}{cosu}+ \frac{cosu}{senu}=\\ &\\ &\\ &\frac{sen^2u+\cos^2u}{senu·cosu}=\frac{1}{senu·cosu}\\ &\\ &\\ &\\ &\text{Y en el lado derecho}\\ &\\ &\frac{1}{cosu}·\frac{1}{senu}=\frac{1}{senu·cosu}\\ &\\ &\\ &\\ &\text{Luego es cierta la identidad}\end{align}$$
Y eso es todo.